# sin(2x)-sin(2y)=0

## Simple and best practice solution for sin(2x)-sin(2y)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for sin(2x)-sin(2y)=0 equation:

Simplifying
sin(2x) + -1sin(2y) = 0
Remove parenthesis around (2x)
ins * 2x + -1sin(2y) = 0
Reorder the terms for easier multiplication:
2ins * x + -1sin(2y) = 0
Multiply ins * x
2insx + -1sin(2y) = 0
Remove parenthesis around (2y)
2insx + -1ins * 2y = 0
Reorder the terms for easier multiplication:
2insx + -1 * 2ins * y = 0
Multiply -1 * 2
2insx + -2ins * y = 0
Multiply ins * y
2insx + -2insy = 0
Solving
2insx + -2insy = 0
Solving for variable 'i'.
Move all terms containing i to the left, all other terms to the right.
Factor out the Greatest Common Factor (GCF), '2ins'.
2ins(x + -1y) = 0
Ignore the factor 2.
Subproblem 1Set the factor 'ins' equal to zero and attempt to solve:
Simplifying
ins = 0
Solving
ins = 0
Move all terms containing i to the left, all other terms to the right.
Simplifying
ins = 0
The solution to this equation could not be determined.
This subproblem is being ignored because a solution could not be determined.
Subproblem 2Set the factor '(x + -1y)' equal to zero and attempt to solve:
Simplifying
x + -1y = 0
Solving
x + -1y = 0
Move all terms containing i to the left, all other terms to the right.
Add '-1x' to each side of the equation.
x + -1x + -1y = 0 + -1x
Combine like terms: x + -1x = 0
0 + -1y = 0 + -1x
-1y = 0 + -1x
Remove the zero:
-1y = -1x
Add 'y' to each side of the equation.
-1y + y = -1x + y
Combine like terms: -1y + y = 0
0 = -1x + y
Simplifying
0 = -1x + y
The solution to this equation could not be determined.
This subproblem is being ignored because a solution could not be determined.
The solution to this equation could not be determined.`